f(x) = 32x + 12x - 2xx
f(3) =
nt : Yey ermpz kembali s.a.i.n.g.a.n Pedo ada saya senang sekali :v
- f(x) = 32x + 12x - 2xx
- f(3) = ...
____________________________
f(3) = 32(3) + 12(3) - 2(3)(3)
f(3) = ( 32 × 3 ) + ( 12 × 3 ) - ( 2 × 3 )(3)
f(3) = 96 + 36 - 6(3)
f(3) = 96 + 36 - ( 6 × 3 )
f(3) = 96 + 36 - 18
f(3) = 132 - 18
f(3) = 114
[tex]\huge\tt\color{FF6666}{@}\color{FFB266}{C}\color{B2FF66}{x}\color{66FF66}{y}\color{66FFFF}{z}\color{66B2FF}{a}\tiny \color{pink}{Cherry}[/tex]
penyelesaian :
f(x) = 32x + 12x - 2xx
f(3) = 32(3) + 12(3) - 2(3)3)
f(3) = (32 + 32 + 32) + 12(3) - 2(3)3)
f(3) = (64 + 32) + 12(3) - 2(3)3)
f(3) = 96 + 12(3) - 2(3)3)
f(3) = 96 + (12 + 12 + 12) - 2(3)3)
f(3) = 96 + (24 + 12) - 2(3)3)
f(3) = 96 + 36 - 2(3)3)
f(3) = 96 + 36 - (2 × 3)(3)
f(3) = 96 + 36 - 6(3)
f(3) = 96 + 36 - (6 + 6 + 6)
f(3) = 96 + 36 - (12 + 6)
f(3) = 96 + 36 - 18
f(3) = 132 - 18
f(3) = 114
_____________________
[answer.2.content]